Phase Velocity Estimation of a Microstrip Line in a Stoichiometric Periodically Domain-Inverted LiTaO3 Modulator Using Electro-Optic Sampling Technique. (30th October 2008) - Hisatake, Shintaro; Kaino, Akira; Yasuda, Tomoaki; Nagatsuma, Tadao
Abstract : We estimate the phase velocity of a modulation microwave in a quasi-velocity-matched (QVM) electro-optic (EO) phase modulator (QVM-EOM) using EO sampling which is accurate and the most reliable technique for measuring voltage waveforms at an electrode. The substrate of the measured QVM-EOM is a stoichiometric periodically domain-invertedLiTaO 3 crystal. The electric field of a standing wave in a resonant microstrip line (width: 0.5 mm, height: 0.5 mm) is measured by employing a CdTe crystal as an EO sensor. The wavelength of the traveling microwave at 16.0801 GHz is determined as 3.33 mm by fitting the theoretical curve to the measured electric field distribution. The phase velocity is estimated asv m = 5.35 × 10 7  m/s, though there exists about 5% systematic error due to the perturbation by the EO sensor. Relative dielectric constant ofε r = 41.5 is led as the maximum likelihood value that derives the estimated phase velocity.